Chronic Illness in Pediatric Critical Care - Murphy Salem, Sinead; Graham, Robert J. (Frontiers in Pediatrics, 2021)
Children and Youth with Special Healthcare Needs (CYSHCN), children with medical complexity (CMC), and children with chronic, critical illness (CCI) represent pediatric populations with varying degrees of medical dependance and vulnerability. These populations are heterogeneous in underlying conditions, congenital and acquired, as well as intensity of baseline medical needs. In times of intercurrent illness or perioperative management, these patients often require acute care services in the pediatric intensive care (PICU) setting. This review describes epidemiologic trends in chronic illness in the PICU setting, differentiates these populations from those without significant baseline medical requirements, reviews models of care designed to address the intersection of acute and chronic illness, and posits considerations for future roles of PICU providers to optimize the care and outcomes of these children and their families.